2020
DOI: 10.2106/jbjs.oa.19.00079
|View full text |Cite
|
Sign up to set email alerts
|

Protocatechuic Acid as a Topical Antimicrobial for Surgical Skin Antisepsis

Abstract: Background: There is a need for novel skin antiseptic agents to combat the health-care burdens associated with surgical site infection (SSI) and bacterial resistance. The purpose of this proof-of-principle pilot study was to investigate the potential of the phenolic compound protocatechuic acid (PCA) as a topical antimicrobial for surgical skin antisepsis. Methods: The Kirby-Bauer method of disc diffusion was used to investigate the in vitro antimicrobial activity and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The daily application of 78 mM topical PCA resulted in an approximately 13.8-times lower C. acnes load in harvested skin specimens compared with untreated mice. However, both lower doses (39 and 19.5 mM) failed to show an effect 12 . In agreement with the findings of Zillich et al, these experiments suggested that the skin penetrative properties of topical PCA were dose-dependent and that increasing doses could improve the antimicrobial activity of topical PCA against dermal C. acnes loads in living skin.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…The daily application of 78 mM topical PCA resulted in an approximately 13.8-times lower C. acnes load in harvested skin specimens compared with untreated mice. However, both lower doses (39 and 19.5 mM) failed to show an effect 12 . In agreement with the findings of Zillich et al, these experiments suggested that the skin penetrative properties of topical PCA were dose-dependent and that increasing doses could improve the antimicrobial activity of topical PCA against dermal C. acnes loads in living skin.…”
Section: Discussionmentioning
confidence: 82%
“…In other work by our group, we performed antimicrobial susceptibility testing of PCA and 7 related phenolic compounds against several common pathogens. Compared with related compounds, PCA demonstrated the broadest spectrum of antimicrobial activity, including efficacy against organisms including S. aureus, methicillin-resistant S. aureus (MRSA), Pseudomonas aeruginosa, and C. acnes, among others 12 . These findings suggest that PCA was the likely active antimicrobial component seen in prior food-plant-based studies, and help to identify its potential for clinical application in the treatment of skin and wound pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations